The Swiss vocational education and training system: What can Spain learn from Switzerland? - Maria Esther Egg; Ursula Renold (ETH Zurich, KOF Swiss Economic Institute, 2015)
Switzerland is famous for its vocational education and training (VET) system. This article describes Switzerland's success in integrating adolescents into the labour market, with emphasis on two aspects. First, dual-track VET, which combines learning at school and in host companies, is an attractive choice for adolescents. It prepares them for the labour market and for progression routes to higher education. Second, the firm's decision to train could be an example of the prisoner's dilemma, but Switzerland has managed to sidestep that issue and minimize concerns about poaching. Finally, we discuss what Spain could learn from the Swiss VET system.
Keywords: C71; I21; 330; Swiss vocational education and training system; apprenticeship; standard of excellence; youth labour market; prisoner's dilemma